Burnout syndrome in physicians of the Hipolito Unanue National Hospital in Lima - Peru, 2018. - Chilquillo-Vega, Vera L. (2019)
Objectives: To identify the prevalence and factors associated with the Burnout Syndrome (BOS) in physicians of the Hipólito Unanue National Hospital in Lima-Peru, during 2018. Material and methods: Observational, transversal and analytical study. The initial study population was constituted by 252 doctors. A sample was selected by the stratified random sampling technique. Different socio-demographic and labor variables were recorded through an anonymous survey. For the diagnosis of BOS, the Maslach Burnout Inventory was used. The variables associated were determined by means of a logistic regression model. A value of p <0.05 was considered significant. Results: Out of 150 doctors surveyed, 23 (15.3%) showed results compatible with BOS. Sixty-five (43.3%) of the respondents reached a high level of emotional exhaustion, 69 (46%) a high level of depersonalization, and 61 (41.7%) a low level of personal accomplishment (p <0.05). The variables associated with the BOS were male sex (OR = 6.12; 95% CI: 1.43-26.13, p = 0.01) while having an additional job (OR = 0.15; 95% CI: 0.04 - 0.49, p = 0.002), could be considered a protective factor. Conclusions: A low prevalence of BOS was found among the physicians surveyed, although a significant group of them reported high levels of emotional exhaustion and depersonalization with low levels of personal accomplishment. Male sex was associated with BOS, while having an additional job showed a possible protective effect.